PENGARUH KEPUASAN KERJA DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT. PATRA DRILLING CONTRACTOR AIR SERDANG PENINJAUAN KAB. OGAN KOMERING ULU - Erfin Mardalena; Riki Adriant; Wayan Agus Indrawan (Ekonomika, 2024)
This study aimed to determine The Influence of Job Satisfaction and Job Loyalty on Employees' Performance at PT. Patra Drilling Contactor Air Serdang Peninjauan, Ogan Komering Ulu. The data used was primary and secondary data. The analysis used was multiple linear regression analysis. The results of the T test and F test showed that there was an influence of job satisfaction and work loyalty on employees' performance at PT. Patra Drilling Contractor Air Serdang Peninjauan, Ogan Komering Ulu either partially or simultaneously. The R square figure was 0.403, this showed that the proportion of overall variation in the value of the employees' performance variable (Y) which could beex plain edorca used by the linear relation ship between the variab les Job Satisfaction (X1) and Job Loyalty was 40.3% while the remaining 59.7% was explained by other variab les that were not included in this research model, namely Ability and Expertise, Knowledge, Work Design, Personality, Work Motivation, Leadership, Leadership Style, Organizational Culture, Work Environment, Commitment, Work Discipline.